Komunikasi Lingkungan untuk Mitigasi Bencana Erupsi Gunung Sinabung - Puji Lestari; Sari Bahagiarti Kusumayudha; Eko Teguh Paripurno; Berliyan Ramadhaniyanto (Jurnal Aspikom)
This study aims to find a model of environmental communications for disaster mitigation eruption of Mount Sinabung at Karo district of North Sumatra. This research also aims at increasing public awareness and government in improving the effectiveness of disaster communications in Sinabung. Organizational Information Theory is used as concept of his study. The research uses descriptive qualitative method by employing data collection techniques such as Focus Group Discussion (FGD) and interviews on communication training for disaster mitigation at Sinabung. The research located in Karo district of North Sumatra, particularly at Regional Disaster Management Agency (BPBD), Department of Communication and Information Technology, and Kesbanglinmas, Head sub district, Head of village, and volunteers. The result of this research is a model of environmental communications to support early warning system in Sinabung.